Production of high‐purity hydrogen and layered doubled hydroxide by the hydrolysis of Mg‐Al alloys - Zheng, Tong; Zhang, Jingqi; Tang, Yang; Wan, Pingyu; Yuan, Qipeng; Hu, Hanjun; Coulon, Frederic; Hu, Qing; Yang, Xiao Jin (Wiley, 2021)
Hydrogen is becoming an important clean energy and layered doubled hydroxide (LDH) is of great interest for many applications, including water treatment, environmental remediation, and chemical catalysis. The production of high‐purity hydrogen and LDH by the hydrolysis of Mg‐Al alloys is reported. The effects of initial pH, reaction temperature, reaction time, and alloy's Mg/Al mass ratio on the rate of hydrogen generation and the purity of LDH are evaluated and the solid hydrolysis products are characterized by different techniques. The initial rate of hydrogen generation increases with decreasing initial pH and increasing reaction temperature and Mg/Al ratio while the purity of LDH increases with Mg/Al ratio, reaction temperature and time. This study may provide a new, green, and sustainable approach for storage of hydrogen and material for water treatment.
Keywords: Sustainable development; Layered doubled hydroxide,; Hydrogen storage; Alloys